2021
DOI: 10.5194/acp-21-8413-2021
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional impacts of land cover changes on isoprene emissions derived from spaceborne data and the MEGAN model

Abstract: Abstract. Among the biogenic volatile organic compounds (BVOCs) emitted by plant foliage, isoprene is by far the most important in terms of both global emission and atmospheric impact. It is highly reactive in the air, and its degradation favours the generation of ozone (in the presence of NOx) and secondary organic aerosols. A critical aspect of BVOC emission modelling is the representation of land use and land cover (LULC). The current emission inventories are usually based on land cover maps that are either… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 102 publications
3
38
0
Order By: Relevance
“…When annually changing ESA-CCI data are implemented, the trend decreases to 0.24 % yr -1 . Similar observation was made by Opacka et al (2021), who used a modified MODIS land cover data in the MEGAN-MOHYCAN emission model to study the impact of land cover change on isoprene emissions. They found a 0.04 to 0.33 % yr -1 mitigating effect of land cover change on general positive trends of isoprene induced mainly by temperature and solar radiation.…”
Section: Impact Of Land Cover Change On Isoprene Emissionssupporting
confidence: 53%
“…When annually changing ESA-CCI data are implemented, the trend decreases to 0.24 % yr -1 . Similar observation was made by Opacka et al (2021), who used a modified MODIS land cover data in the MEGAN-MOHYCAN emission model to study the impact of land cover change on isoprene emissions. They found a 0.04 to 0.33 % yr -1 mitigating effect of land cover change on general positive trends of isoprene induced mainly by temperature and solar radiation.…”
Section: Impact Of Land Cover Change On Isoprene Emissionssupporting
confidence: 53%
“…The discrepancy could be related to the large deforestation rates observed in the humid primary forests located within a radius of 150 km around the city (Hansen et al 2013). When considering the effects of land use changes on isoprene fluxes (Opacka et al 2021), the isoprene emissions around Phnom Penh over 2005-2019 are found to decline by about 1% yr −1 , suggesting that the trend in HCHO columns might be partly due to forest loss in the regions surrounding Phnom Penh.…”
Section: Discussionmentioning
confidence: 97%
“…Satellite observations of formaldehyde columns in the troposphere have been extensively reported in the literature from a number of nadir UV sensors, e.g. the Global Ozone Monitoring Experiment (GOME; Chance et al, 2000;Palmer et al, 2001;De Smedt et al, 2008), SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY; Wittrock et al, 2006;De Smedt et al, 2008, Ozone Monitoring Instrument (OMI;De Smedt et al, 2015Kaiser et al, 2018;Levelt et al, 2018), Global Ozone Monitoring Experiment-2 (GOME-2; De Vrekoussis et al, 2010;Hewson et al, 2013;Hassinen et al, 2016) and Ozone Mapping and Profiler Suite (OMPS; Li et al, 2015;González Abad et al, 2016). They are used in many studies related to air quality and climate change (e.g.…”
Section: Introductionmentioning
confidence: 99%